The urgent case for stronger climate targets for international shipping. (16th March 2022) - Bullock, Simon; Mason, James; Larkin, Alice
ABSTRACT: International shipping is overwhelmingly reliant on fossil fuels, with annual carbon dioxide emissions equivalent to a country the size of Germany. Actions to reduce its emissions are therefore an important element of global efforts to combat climate change. This article re-assesses the international shipping sector's initial greenhouse gas emissions reduction targets against the Paris Agreement goals. The analysis is based upon the latest data from the Intergovernmental Panel on Climate Change (IPCC) and International Maritime Organization (IMO) and uses the concept of carbon budgets to evaluate proportionate 1.5°C emissions pathways for the sector. The consequences of the resulting Paris-compliant pathways for shipping's existing mitigation targets and strategy are discussed. The article concludes that significantly stronger short- and longer-term targets need to be set for the sector to be compatible with the Paris Agreement's goals: 34% reductions on 2008 emissions levels by 2030, and zero emissions before 2050, compared with the sector's existing target of a 50% cut in CO2 by 2050. Crucially, strengthening the target by the IMO's strategy revision date of 2023 is imperative. The long asset lifetimes of ships and shipping infrastructure limit the speed of transition such that a delay of even a few years will dictate an untenable rate of decarbonization and increased risk of pushing the already challenging Paris goals out of reach. Key policy insights There is a gap between targets set out in the IMO's Initial Strategy and what is needed by the shipping sector to be Paris-compliant. Paris-compliant targets require a 34% reduction in emissions by 2030, with zero emissions before 2050. Existing targets imply no absolute reduction in emissions to 2030, and only a 50% reduction by 2050. The longer the delay in setting new targets, the steeper subsequent decarbonization trajectories become. Delay beyond 2023 would necessitate an untenably rapid transition, given long shipping asset lifetimes and global requirements for new land-side infrastructures, increasing the mitigation burden on other sectors. COP26 in November 2021 is an opportunity for the shipping sector to signal its intent to strengthen its targets, and to implement this in its 2023 strategy revision process, at the latest.